2019
DOI: 10.14569/ijacsa.2019.0100464
|View full text |Cite
|
Sign up to set email alerts
|

Content based Document Classification using Soft Cosine Measure

Abstract: Document classification is a deep-rooted issue in information retrieval and assumed to be an imperative part of an assortment of applications for effective management of text documents and substantial volumes of unstructured data. Automatic document classification can be defined as a contentbased arrangement of documents to some predefined categories which is for sure, less demanding for fetching the relevant data at the right time as well as filtering and steering documents directly to users. For recovering d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…But unlike cosine similarity, the features are projected in an n-dimensional space so that similar features are close by with very less angle difference. This causes the meaningfully similar words (features) of vectors (questions) to have minimal angle differences ( Hasan et al, 2019 ), as shown in Fig. 11 .…”
Section: Guiding the Learner To The Probable Correct Questionmentioning
confidence: 99%
“…But unlike cosine similarity, the features are projected in an n-dimensional space so that similar features are close by with very less angle difference. This causes the meaningfully similar words (features) of vectors (questions) to have minimal angle differences ( Hasan et al, 2019 ), as shown in Fig. 11 .…”
Section: Guiding the Learner To The Probable Correct Questionmentioning
confidence: 99%